Simulation of Flow in Porous Media : Applications in Energy and Environment. - Kraus, Johannes (Radon series on computational and applied mathematics., 2013)
Thisbook is the firstvolume of three volume series recording the""Radon Special Semester 2011 on Multiscale Simulation & Analysis in Energy and the Environment"" taking placein Linz, Austria, October 3-7, 2011. Thevolume discusses new developments in computational methods for the simulation of flows in porous media with applications in waste storage, CO2 sequestration and fuel cells. It records the achievements of Workshop 1 ""Simulation of Flow in Porous Media and Applications in Waste Management and CO2 Sequestration"". Itbrings together key numerical mathematiciansfrom the fields ofanalysis a.